Estudio del sistema de alcantarillado sanitario y pluvial para la cooperativa de vivienda Chimborazo perteneciente a la parroquia El Rosario, cantón Guano - Moreano Erazo, José Luciano (2013)
In the present study summarizes the results obtained during the development of the project called STUDY limit SANITARY SEWER SYSTEM AND RAIN TO THE COOPERATIVE HOUSING OWNED CHIMBORAZO ROSARY PARISH, CANTON GUANO. Through scientific research using modern methods and techniques: subjective and objective, which was to survey techniques, interviews, measurement, observation, and data analysis addressed the results thereof. Who said the current problems experienced by the population of the parish El Rosario for accelerated accretion of the same and other surrounding communities. Having checked and according to the problem in the El Rosario Guano Canton Chimborazo Province and by not having this cooperative with rain healthcare system according to the needs of basic infrastructure and considering the economic development of this sector has designed this system to providing quality service for a better future progress that this aimed at socio-economic development always ensuring basic services. Applying the rules for the good life of the society as stated in Article 107 of the LOES………